Dielectric properties of Fe doped hydroxyapatite prepared by sol-gel method - Kaygili, Omer; Dorozhkin, Sergey V.; Ates, Tankut; Al-Ghamdi, Ahmed A.; Yakuphanoğlu, Fahrettin (Elsevier Sci Ltd, 2014)
Iron-doped hydroxyapatite (HAp) samples with variable amounts of Fe were synthesized and their properties were investigated. Namely, the structure and composition of the prepared samples were analyzed using X-ray diffraction (XRD), Fourier transform infrared (FUR) spectroscopy, scanning electron microscopy (SEM) and energy dispersive X-ray (EDX) techniques. In addition, the dielectric and alternating current conductivity properties were investigated at room temperature. The samples were found to consist of a high crystalline HAp with a minor admixture of beta-tricalcium phosphate (beta-TCP). With increasing amount of Fe, the crystallite sizes of the samples were found to gradually decrease from 32.54 rim to 27.91 rim with simultaneous changes in the crystallinity degree, lattice parameters, unit cell volume and the phase composition. The fine-grained microstructure was observed and EDX analysis confirmed Fe-substitution in the apatitic structure because the Ca/P molar ratios were gradually decreased from 1.68 to 1.35 by addition of Fe. The alternating current conductivity confirmed that Fe doped HAp samples exhibited the insulator behavior. The relative permittivity of the HAp was increased with the addition of Fe. The samples exhibited a non-Debye relaxation mechanism. (C) 2014 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: Dielectric permittivity; Dielectric relaxation; Fe-doping; Hydroxyapatite